Parametric control of technical preproduction process on dispersed enterprise - Бабіч, К. С. (Proceedings of National Aviation University (archive), 2013)
The technical preproduction process control parameters determining was discussed. The place of technical preproduction control module in machinery enterprises information environment structure was determined. On the basis of expertise a set of control parameters was suggested. These parameters completely describe the technical preproduction process control in informational environment of enterprise. The values of parameters were formalized. So technical preproduction process control may be executed in optimal way